Intimate Partner Violence and HIV-risk Behaviors: Evaluating Avoidant Coping as a Moderator - Weiss, Nicole H. (AIDS Behav, 2017)
Women who experience intimate partner violence (IPV) report higher rates of HIV-risk behaviors. However, few studies have examined factors that may influence the strength of the link between IPV and HIV-risk behaviors. The goal of the current study was to extend extant research by evaluating the potential moderating role of avoidant coping in this relation. Participants were 212 women currently experiencing IPV (M age = 36.63, 70.8% African American) who were recruited from the community. Significant positive associations were found between physical, psychological, and sexual IPV severity and both avoidant coping and HIV-risk behaviors. Avoidant coping moderated the relations between both physical and psychological IPV severity and HIV-risk behaviors, such that physical and psychological IPV severity were significantly associated with HIV-risk behaviors when avoidant coping was high (but not low). Findings underscore avoidant coping as an important factor in identifying and subsequently treating IPV-victimized women vulnerable to HIV-risk behaviors.